Fedora Bible 2011 edition : featuring Fedora Linux 14 - Negus, Chris, 1957-; Foster-Johnson, Eric (Bible., 2011)
Get all the essentials of the major changes in Fedora 14 Veteran authors Christopher Negus and Eric Foster-Johnson provide you with a thorough look at the skills needed to master the latest version of Fedora and Red Hat Linux. Their step-by-step instructions walk you through a painless and simple installation of Linux; then you'll explore the major changes to the release of Fedora 14 while also revisiting the previous version so you can see what features have been updated and revised. Focuses on the essentials of the updated and new elements of Fedora Linux 14Address.